2016
DOI: 10.15690/vramn586
|View full text |Cite
|
Sign up to set email alerts
|

The Possibilities of Cell Technologies in the Treatment of Cicatricial Lesions of the Vocal Folds

Abstract: The article is a brief review of publications devoted to the problem of persistent dysphonia. The main cause of voice disorders is the scarring of the vocal folds resulting from trauma, surgical manipulation, inflammatory process. Treatment of cicatricial lesions of the vocal folds remains a challenge, as far as existing methods do not ВведениеГолос -основной способ общения, необходимый для адаптации человека в окружающей среде и социаль-ной реализации. Нарушение голосовых функций имеет значительные негативные… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
2
0
1
Order By: Relevance
“…The parameters of the inflicted defect and the time of the scar maturation were optimal, because, according to the literature data, the depth of a defect must exceed the actual thickness of the vocal fold's lamina propria, as a trauma to the deep layers unavoidably leads to the cicatricial changes with the subsequent deterioration of the vibratory characteristics. Three months is a sufficient time for the completion of the active processes of collagen organisation in the scar tissue (Svistushkin et al, 2016).…”
Section: Creation Of a Defect In The Vocal Foldsmentioning
confidence: 99%
“…The parameters of the inflicted defect and the time of the scar maturation were optimal, because, according to the literature data, the depth of a defect must exceed the actual thickness of the vocal fold's lamina propria, as a trauma to the deep layers unavoidably leads to the cicatricial changes with the subsequent deterioration of the vibratory characteristics. Three months is a sufficient time for the completion of the active processes of collagen organisation in the scar tissue (Svistushkin et al, 2016).…”
Section: Creation Of a Defect In The Vocal Foldsmentioning
confidence: 99%
“…Therefore, great interest arose to the techniques and approaches of regenerative medicine for the development of an efficient way of treatment for VF scar lesions [ 15 19 ]. In experimental studies, positive effects of cells from various sources have been demonstrated, such as the reduction in general fibrosis signs, level of inflammation, thickness of the scar tissue, restoration of the extracellular matrix architecture and the tissues’ mechanical parameters [ 20 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…у взрослых и 3 мес. -у детей) антибактери-альной терапии как факта риска инфекций, вызванных резистентными возбудителями [16]. Вопросы при выборе антибиотика согласно стандарту ■ стартовый антибиотик, ■ доза антибиотика, ■ форма, ■ безопасность, ■ комплаентность, ■ вероятность соблюдения рекомендованной длитель-ности терапии.…”
unclassified